Is it acceptable for people to be paid to adhere to medication? No - Shaw, Joanne (BMJ Publishing Group Ltd., 2007)
Plans to give drug users shopping vouchers to attend treatment programmes and stay clean have been unveiled by NICE. Joanne Shaw believes that payment creates perverse incentives, whereas Tom Burns says rewarding patients for cooperation is consistent with good medical practice